2008
DOI: 10.1109/tmi.2008.922185
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Positron Emission Tomography Data-Driven Analysis Using Sparse Bayesian Learning

Abstract: Abstract-A method is presented for the analysis of dynamic positron emission tomography (PET) data using sparse Bayesian learning. Parameters are estimated in a compartmental framework using an over-complete exponential basis set and sparse Bayesian learning. The technique is applicable to analyses requiring either a plasma or reference tissue input function and produces estimates of the system's macro-parameters and model order. In addition, the Bayesian approach returns the posterior distribution which allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…The V T estimates by FPCA are about 12.4% lower than those by DEPICT, while pDEPICT was similar to that of DEPICT (approximately 2.2% lower, data not shown). Positive biases of 10% or more are not uncommon for parameter values in the range of those present here (bias is parameter dependent) for PET compartmental models when analyzed with spectral analysis (see Peng et al 2008 ), and as such the estimates provided by FPCA are closer to what might be expected from previous simulation results. Thus, the FPCA yields results which are more quantitatively plausible for comparison across a population.…”
Section: Measured 11 C-diprenorphine Datasupporting
confidence: 83%
See 2 more Smart Citations
“…The V T estimates by FPCA are about 12.4% lower than those by DEPICT, while pDEPICT was similar to that of DEPICT (approximately 2.2% lower, data not shown). Positive biases of 10% or more are not uncommon for parameter values in the range of those present here (bias is parameter dependent) for PET compartmental models when analyzed with spectral analysis (see Peng et al 2008 ), and as such the estimates provided by FPCA are closer to what might be expected from previous simulation results. Thus, the FPCA yields results which are more quantitatively plausible for comparison across a population.…”
Section: Measured 11 C-diprenorphine Datasupporting
confidence: 83%
“…Presmoothing decreases the noise in the data, hence can reduce overall potential biases in further analysis, as even though smoothing itself introduces a small bias, in many nonlinear situations, parameter or functional biases can be noise level dependent. In parametric nonlinear models such as compartmental models, this is well known (Peng et al 2008 ), while here the errors in the observed functions are somewhat similar to those in measurement error models, which yield biases in traditional regression analysis. The presmoothing also produces functions that are smoother than the original data, making subsequent deconvolution easier, as large independent measurement errors tend to result in considerable instability in deconvolution settings.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Positron emission tomography (PET) image reconstruction methods based on list-mode acquisition have many advantages compared with those using sinograms, especially for time-of-flight (ToF), 1-3 high resolution, 4,5 and dynamic 6 PET data. List-mode data can be reconstructed using iterative algorithms such as maximum likelihood expectation maximization (MLEM) (Ref.…”
Section: Introductionmentioning
confidence: 99%
“…However, the definition of an adequate penalty function to use in practice has proved to be difficult. This concept was further developed by Gunn and colleagues in 2002 and it originated what are now called basis pursuit methods [31, 32]. In 1994, Turkheimer and colleagues proposed a high-pass filter for equilibrating components, with the aim of improving estimates of α 0 and thus determining a more accurate and precise estimate of regional cerebral metabolic rate for glucose in PET studies [21].…”
Section: Methods Implementationmentioning
confidence: 99%